Analisis Efisiensi Menggunakan Metode Data Envelopment Analysis (Dea) (Kasus Pada PT. Indonesia Toray Sinthetic) - Nur Halimatu Sa'diyah (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The aim of this research are (1) to know the efficiency of machine 1, machine 2, machine 3, and machine 4 and to know which machines that have the highest efficiency; (2) to know which year that have the highest efficiency. The analysis result of efficeincy of PT.ITS with the dmu is machine, shows that the efficiency condition of the machine during five years since 2011 until 2015 generally can be considered to have a perfect efficiency (efficiency = 1).From the five years, there are only 5 occurance of imperfectefficiency which are spread in all the machines.The order of the most efficient Kiln to the least is machine 3, machine 4, mqchine1, and then machine 2.Meanwhile for the annual analysis, theorder of the most efficient year to the least is 2014, 2012, 2013, 2015, and then 2011.